Revision hip arthroplasty: principles of management and surgical techniques - Judas, F (2012)
Total hip arthroplasty is one of the most successful orthopaedic procedures and is highly effective in relieving pain and improving function. With time, some joint replacements may require revision, mainly because of mechanical loosening and instability, and also when pain, swelling, limp, stiffness become too great. On the other hand, there is an increased failure rate with longer follow-up of revision total hip replacement, and that progressive radiolucency at an interface indicates a poor prognosis for the arthroplasty. A major problem in revision surgery is the loss of bone stock due to particulate debris, stress shielding, fracture, or infection and the consequent difficulty in reconstructing a stable joint. Loss of bone stock has been widely treated using bone autografts, bone allografts and bone graft substitutes. Allograft tissue is used in almost all of the orthopaedic surgical subspecialties. Cryopreserved cancellous, cortical and massive osteochondral human bone allografts are used to reconstruct bone defects with osteolysis secondary to loosening of total hip arthroplasties. Several studies have confirmed, both clinically and histologically, the incorporation of fragmented cryopreserved impacted allografts used in acetabular and femoral revision surgery. Surgical planning is indicated for every revision hip arthroplasty, whether it is a straightforward or a complicated case. The preoperative planning is defined in the outpatient clinic and should be repeated just before surgery. Templating may allow the surgeon to predict intraoperative difficulties and possible complications. An accurate preoperative planning is required to reduce surgical time, minimize risks, decrease the stress level of the entire surgical team and increase the rate of the successful outcomes for patients. Special instruments and tools are necessary to removal the failed prosthetic components, minimizing the risk of bone loss, bone fracture and excessive bleeding. The aims of surgical procedures are to restore the bone stock, the center of hip rotation, the offset, the leg length and to obtain optimal alignment of the implants.